PENGARUH PEMBERIAN PUPUK BOKASHI DAN PUPUK MAJEMUK NPK PHONSKA TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Budi Prasetyo Yudo dan Abdul Fatah (Universitas 17 Agustus 1945 Samarinda, 2014)
Objective of the research was to study the effect of Bokashi and Phonska NPK compound fertilizer on the growth of cocoa seedling and to find out the best interaction between them on the cocoa seedling. The research was carried out in Tutung Village, Linggang Bigung Sub District of West Kutai Regency, East Kalimantan Province. It lasted for about four months (February 2013 to May 2013). The Completely Randomised Design was employed for this research with factorial 4 x 4 and 4 replications. The first factor was Bokashi (B), consisted of 4 sub factors: No Bokashi application (b0), 10 ton Bokashi/ha or equal to 5 gram/polybag (b1), 20 ton Bokashi/ha or equal to 10 gram/polybag (b2,), and 30 ton Bokashi/ha or equal to 15 gram/polybag (b3). And the second factor was application of Phonska NPK compound fertilizer on the cocoa seedling (P) that consisted of 4 sub-factors: no Phonska npk compound fertilizer aapplication (P0), 1 g Phonska NPK compound fertilizer/polybag (p1), 2 g Phonska NPK compound fertilizer/polybag (p2), 3 g Phonska NPK compound fertilizer/polybag (p3).Results of the research indicated that the application of Bokashi and Phonska NPK compound fertilizer, as well as their interaction did not effect significantly at all on all parameters observed, namely seedling height, leave number, and stem diameter at 1-,2-, and 3-month old.